Genome-Wide Association and Functional Studies Identify SCML4 and THSD7A as Novel Susceptibility Genes for Coronary Artery Disease. Issue 4 (April 2018) - Li, Yang; Wang, Dao Wen; Chen, Yundai; Chen, Can; Guo, Jian; Zhang, Shu; Sun, Zhijun; Ding, Hu; Yao, Yan; Zhou, Lei; Xu, Ke; Song, Chun; et al.
Abstract : Objective—: The genetic contribution to coronary artery disease (CAD) remains largely unclear. We combined genetic screening with functional characterizations to identify novel loci and candidate genes for CAD. Approach and Results—: We performed genome-wide screening followed by multicenter validation in 8 cohorts consisting of 21 828 participants of Han ethnicity and identified 3 novel intragenic SNPs (single nucleotide polymorphisms), rs9486729 ( SCML4 [Scm polycomb group protein-like 4]; odds ratio, 1.25; 95% CI, 1.17–1.34; P =3.51×10 −11 ), rs17165136 ( THSD7A [thrombospondin type 1 domain-containing 7A]; odds ratio 1.28; 95% CI, 1.21–1.35; P <1.00×10 −25 ), and rs852787 ( DAB1 [disabled-1]; odds ratio, 1.29; 95% CI, 1.21–1.38; P =2.02×10 −14 ), associated with CAD with genome-wide significance. The risk allele of rs9486729 and protective allele of rs17165136 were associated with the decreased expression of their host genes, SCML4 and THSD7A, respectively, whereas rs852787 did not have transcriptional effects on any gene. Knockdown of SCML4 activated endothelial cells by increasing the expression of IL-6, E-selectin, and ICAM and weakened their antiapoptotic activity, whereas the knockdown of THSD7A had little effect on these endothelial cell functions but attenuated monocyte adhesion via decreasing the expression of ICAM, L-selectin, and ITGB2 . We further showed that inhibiting the expression of SCML4 exacerbated endothelial dysfunction and vascular remodeling in a rat model with partial carotid ligation. Conclusions—: We identify 3 novel loci associated with CAD and show that 2 genes, SCML4 and THSD7A, make functional contributions to atherosclerosis. How rs852787 and its host gene DAB1 are linked to CAD needs further studies. Abstract : Supplemental Digital Content is available in the text.